Modeling and simulation of the industrial sequencing batch reactor wastewater treatment process for cleaner production in pulp and paper mills. (20th November 2017) - Man, Yi; Shen, Wenhao; Chen, Xiaoquan; Long, Zhou; Pons, Marie-Noëlle
Abstract: Being an internationally accepted standard for the activated sludge modeling, the Activated Sludge Model No.1 (ASM1) was used to simulate the treatment of paper mills effluent in an industrial full-scale sequencing batch reactor (SBR). Key characteristic parameters were estimated and corrected with the wastewater temperature: maximum heterotrophic growth rate μ H (9.69/day), heterotrophic yield Y H (0.625 g cell COD/g COD oxidized) and heterotrophic decay rate b H (1.98/day). The wastewater chemical oxygen demand (COD) was fractionated as slowly biodegradable substrate X S (20%), particulate inert organic matter X I (58%), readily biodegradable substrate S S (18%) and soluble inert organic matter S I (4%). Finally, the SBR operation was simulated with field data from the paper mill. The average relative error of the simulated effluent COD was 12.7%. The results showed that the ASM1 could be reasonably used in the papermaking wastewater treatment simulation. Highlights: An industrial SBR simulation model for paper mills was developed. Sludge characteristic parameters were estimated and corrected with temperature. Four COD fractions of the wastewater in paper mill were determined. Simulated results with the field data could predict well the actual effluent COD.